Thrombotic antiphospholipid syndrome: Recurrent thromboses - Tatiana M. Reshetnyak; Fariza A. Cheldieva; Svetlana I. Glukhova; Kamila S. Nurbaeva; Nataliya V. Seredavkina; Mariya V. Cherkasova; Alexander M. Lila; Evgeny L. Nasonov (Научно-практическая ревматология)
Thrombotic antiphospholipid syndrome (APS) is a condition affecting young people in whom a thromboembolic event occurs in the presence of circulating antiphospholipid antibodies (aPL).The aim of this study was the evaluation of the incidence of recurrent thrombosis and its risk factors in antiphospholipid syndrome.Material and methods. The retrospective study included 98 patients with aPL who were followed up at the institute from 2014 to 2023, of whom 66 (67%) were women and 32 (33%) were men. Of the 98 patients with aPL, 48 (49%) had a diagnosis of systemic lupus erythematosus (SLE). Antiphospholipid antibodies (aPL), including antibodies to cardiolipin (IgG/IgM aCL), antibodies to ß2-glycoprotein 1 (IgG/IgM aß2GP1), antibodies to ß2-glycoprotein IgG against domain 1 (IgG aß2GP1-D1), antibodies to phosphatidylserine/prothrombin complex (IgG/ IgM aPS/PT) and other thrombotic risk factors. aPL was assessed by enzyme-linked immunosorbent assay (ELISA) and chemoluminescence assay (CHLA).Results. Thrombosis recurrence was reported in 62 (63%) of 98 patients, and 36 (35%) did not. The main cause of recurrent thrombosis was treatment with direct oral anticoagulants (DOACs). 24 (38.7%) of 62 patients with recurrent thrombosis were treated with DOACs, the duration of which ranged from 6 to 24 months. The next most common cause of recurrent thrombosis was the lack of continuous anticoagulant therapy in 20 (32.5%) of the patients. In 17 (27.4%) of the patients, the recurrence occurred while they were still taking warfarin. In 10 (41.7%) of the 24 patients, the recurrent thrombosis was arterial in origin. This was associated with recurrent cerebral circulation problems. The level of positivity did not matter, but all had triple IgG aPL positivity. 5 had lupus anticoagulant (LA) at the onset of the disease before anticoagulant use. IgG aPS/PT was most important in association with recurring thrombosis in the ELISA: 45 (72.6%) of 62 patients with recurring thrombosis were positive for IgG aPS/PT, compared with 19 (52.8%) of 36 patients without recurring thrombosis. The detection of all aPL was more frequent in CHMA than in ELISA. However, the definition of aPL in ELISA is recommended according to the latest classification criteria. Triple IgG positivity for aCL of IgG aß2GP1, IgG aß2GP1-D1 and CHMA remained a risk factor for recurrent thrombosis and increased the risk of recurrence more than threefold. Obesity was a risk factor for recurrent thrombosis, with a 5-fold increased risk of recurrent thrombosis in obese compared to non-obese patients (p=0.01).Conclusions. Recurrent thrombosis in APS is largely associated with IgG aCL, IgG aß2GP1, IgG aß2GP1-D1, IgG aPS/PT. Triple IgG aPL positivity in any combination significantly increased recurrent thrombosis risk.The presence of any type of aPL IgG in both ELISA and CHLA influenced the recurrence rate of thrombosis in APS.Obesity was a significant risk factor for recurrent thrombosis.